Reflections on 20 Years of Land-Related Development Projects in Central America : 10 Things You Might Not Expect, and Future Directions - Siegel, P.B. (International Land Coalition, Rome, 2014)
This paper takes a critical view of the challenges that lie ahead for land?related development projects in Central America. Drawing upon several sources of information and types of analysis, including literature reviews, field visits and rapid participatory assessments, along with decades of professional experience, the authors examine land-related development policies and projects over the past two decades in Central America (although monitoring and evaluation is admittedly weak). Reflections on past land?related development policies and projects in Central America are based on their contributions to growth and poverty reduction. The reflections, which are really stylized facts, are presented using a 'top ten list' of things that you might not expect from land policy reforms and projects in post?conflict Central America. In short, for a variety of initially unforeseen reasons, land?related development policies and projects have not fully lived up to expectations in terms of poverty reduction for rural residents, especially not for small farmers (campesinos) and the landless, although positive impacts have been obtained for landholders improving the security of property rights, and have generally exceeded expectations for urban residents. The focus on land administration outcomes (e.g., number of parcels registered) has often managed to bypass areas with land conflicts and/or indigenous peoples and these projects have not necessarily provided incentives for environmentally sound natural resource management. At the same time these projects have achieved institutional reforms and the creation of land information systems which are beginning to enable a new paradigm of multi?purpose territorial management which holds great promise. The lessons learned suggest the need to consolidate a new direction for land policy in Central America, one that is holistic and integrates poverty reduction and development goals, natural resource management, disaster risk management and climate change into a territorial approach stressing local governance and planning. There is a need to differentiate between rural and urban areas and better utilize geographic information systems (GIS) and spatial data that have been key products of land projects. Information systems and various land and resource data gathered by land administration projects provide an excellent foundation for a revised and decentralized approach to sustainable development. The paper concludes with six specific recommendations, which can serve as the basis for future discussions on the direction of future development support to countries' land policies and projects in Central America, and other regions.